Sob a lente da subjetividade: a humanidade em foco - Silva, Elizete Conceição (2009)
When the process of investigation of citizen identity construction and supporting themselves in the cultural question and its related issues, such as otherness, symbolizing, as well as considering that new social order before the o phenomenon of the globalization and the transformations that this presented to the world every day, the individual, in its singularity, has to reorganize and adjust itself according to the moment, and these actions that carries also possibilities of growth, stagnation, as well as retrocession. Parallel to the theoretical and investigative analysis, someone appeals to films, histories of lives of personages who make possible the visualization of facts, otherness, singularities and unit between human beings. promoting a clipping in the work relations its promoted and when inquiring about the moment witnessed by the citizen, the cultural factor and its construction gets the focus on the analysis, as well as the relevance of subjectivity is considered in an agglutinant thought, focusing the search of the knowledge and the promotion of a life with a higher level of conscientiousness and harmonys in the scopes personal and consequently social